Kontekstualisasi Pembelajaran Ilmu Mantik dalam Frasa Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan - Zulkifli, Zulkifli; Rezi, Melisa (Turast: Jurnal Penelitian dan Pengabdian, 2023)
This study explains the contextualization or application of learning Mantiq science in reading the text of statutory regulations or in this case Law Number 1 of 1974. Considering that in the current development, learning Mantiq science has only touched the formalistic realm. This study is library research to conduct an analysis of the text of Law No. 1 of 1974 concerning marriage using Mantiq science. The analysis is based on the book Iydhah al-Mubham by Sheikh Ahmad Damanhuri to examine every word and sentence in the Marriage Law. The question to be answered is how to contextualize the learning of Mantiq science into the text of the Law. The results of this study show that the determination of the composition of the propositions in the articles and paragraphs in Law no. 1 of 1974 and understanding and interpreting the editorial composition of the text of the Law reflects the form of material relations in Mantiq science, namely critical language relations which are reflected in the diction and propositions which are used as articles and verses. It was found that some of the editorial texts of Law no. 1 of 1974 contains propositions that do not follow the Indonesian language based on Enhanced Spelling (EYD) which in principle has the potential for ambiguity.Studi ini menjelaskan tentang kontekstualisasi atau penerapan pembelajaran ilmu Mantiq dalam membaca teks peraturan perundang-undangan atau dalam hal ini adalah Undang-undang Nomor 1 Tahun 1974. Mengingat dalam perkembangan yang ada pembelajaran ilmu Mantiq baru menyentuh ranah formalistik. Studi ini merupakan penelitian kepustakaan (library research) untuk melakukan analisis terhadap teks UU No 1 Tahun 1974 tentang perkawinan dengan ilmu Mantiq. Analisis berpijak pada kitab Iydhah al-Mubham karya Syekh Ahmad Damanhuri untuk memeriksa setiap kata dan kalimat dalam UU Perkawinan.Pertanyaan yang ingin dijawab adalah bagaimana cara mengkontekstualisasikan pembelajaran ilmu Mantiq kedalam teks Undang-undang. Hasil studi ini menunjukkan bahwa penetapan susunan proposisi pada pasal dan ayat di dalam UU No. 1 Tahun 1974 serta memahami dan memaknai susunan redaksi teks UU merefleksikan bentuk relasi materi ilmu Mantiq, yaitu relasi bahasa kritis yang terefleksi dari diksi dan proposisi yang dijadikan sebagai pasal dan ayat. Ditemukan bahwa sebagian redaksi teks UU No. 1 Tahun 1974 menyimpan proposisi yang tidak mengikuti bahasa Indonesia berdasarkan Ejaan Yang Disempurnakan (EYD) yang cecara prinsip berpeluang terjadi ambigusitas.